Parents’ Liability For The Damage Caused By The Child - Burim Tahiri (European Scientific Journal, ESJ, 2016)
Parents’ liability for the damage caused by the child is a kind of liability for the others. Regarding the meaning of the terminology of liability for the others we should say that various authors have used different terminologies, however it is important to be understood that the essence of this liability remains unchangeable to all authors and to all normative acts of various states regulating this kind of liability. Parents’ liability for the damage caused by their child shall mean cases when the parents should compensate the damage caused by their minor child, so when they have been liable for the damage caused by the child. In order that this liability to come into consideration there should be fulfilled the conditions such as: a) Child that causes the damage should be minor, b) Child should be living with one or both parents. It is important to emphasize that parents shall be together liable for the damage caused by their child in cases when they live together, however in cases when they live separately, the parent to whom the child is entrusted for maintenance and care shall be liable for the damage caused by the child. Legal framework has regulated noticeably clear this matter by dividing into categories the parents’ liability for their children. In the first category are all minors up to the age of seven (7) and in this case parents are liable without taking into consideration the fault. A similar regulation is that of Kosovo, Croatia and Serbia while Albania does not have such a regulation. In Albania there are excluded from the liability all minors under the age of fourteen (14) and for the damage caused by them there shall be liable the parents or custodian, so it depends who takes care after them. The second categorization is related to the minors form the age of seven (7) until the age of fourteen (14). In these cases, Kosovo, Croatia and Serbia have determined that parents shall be obliged to be liable for the damage caused by the minor of such age except if they can prove that they are not liable for the damage caused by the child. Hence, we continuously have to do with a similarity in legal framework between Kosovo, Croatia and Serbia regarding the regulation of this liability. The third category shall include the minors from the age of fourteen (14) until the age of eighteen (18) where they shall be liable according to general rules of liability. Regarding the comparative aspects of normative regulation of parents’ liability for the damage caused by the children we should say that Kosovo, Croatia and Serbia have regulated similarly this kind of liability but there are some differences in the legislation of Albania based on which there are categorized differently the minors that are excluded from the liability for the caused damage.